2021
DOI: 10.1177/14648849211023872
|View full text |Cite
|
Sign up to set email alerts
|

News automation, materialities, and the remix of an editorial process

Abstract: Software studies is a research field that focuses on the social and cultural implications of the software. They are grounded by interdisciplinarity, borrowing to digital humanities, cultural studies, or new media studies. Their application domains are as heterogeneous as software can be, from interfaces to new digital mediatic forms. This paper examines the relevance of software studies for journalism studies in the context of automated news production, where technological artifacts can also be understood as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…Other studies have focused on understanding the impact of automated news on media professionals (Danzon-Chambaud; Cornia, 2021; Túñez-López, 2021), the adoption of supervised machine learning in journalism studies (De-Grove; Boghe; De-Marez, 2020), news trust and credibility (Sinatra; Hofer, 2023; Fletcher; Schifferes; Thurman, 2023) as well as the challenges and debates surrounding automated journalism and AI research (De-Lima-Santos; Salaverría, 2021). Additionally, interdisciplinary research fields like software studies have examined the social and cultural implications of software, including its role in automated news production within journalism (Dierickx, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Other studies have focused on understanding the impact of automated news on media professionals (Danzon-Chambaud; Cornia, 2021; Túñez-López, 2021), the adoption of supervised machine learning in journalism studies (De-Grove; Boghe; De-Marez, 2020), news trust and credibility (Sinatra; Hofer, 2023; Fletcher; Schifferes; Thurman, 2023) as well as the challenges and debates surrounding automated journalism and AI research (De-Lima-Santos; Salaverría, 2021). Additionally, interdisciplinary research fields like software studies have examined the social and cultural implications of software, including its role in automated news production within journalism (Dierickx, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Although there are examples of convivial relationship between newsrooms and innovative technologies (e.g., Diakopoulos, 2019; Schapals & Porlezza, 2020), other examples point to apprehension. Dierickx (2019) describes a Belgian newsroom struggling to implement news automation; similarly, Belair‐Gagnon et al (2020) found intrapreneurial units experimenting with chatbots grappling with reconciling tensions between corporate logics and the professional logics of the newsrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Journalism is recognized as a “craft” (Schapals & Porlezza, 2020), comparable to the “craftmanship” of technologists (Passi & Jackson, 2017, p. 2444), and is moved closer to a subjective expert system of the “editorial logic,” with objective decision‐making delegated to the “new knowledge logic” of AI (Gillespie, 2014, p. 192). This redefinition of newswork is ameliorated by framing the generated news as information or service content; “we [can] only describe facts, and you need more than that to be a good editor” (P4) (e.g., Carlson, 2015; Dierickx, 2019; Sirén‐Heikel et al, 2019).…”
Section: Competing and Assimilating Logicsmentioning
confidence: 99%